Origin and early evolution of comet nuclei : workshop honouring Johannes Geiss on the occasion of his 80th birthday - Schulz, R. (Springer, 2017)
In this introductory presentation, material is categorized according to our state of knowledge: What do we know, what do we think we know but don’t know certainly, and what do we not know but often describe it as if it were a well-established fact about comets, their nuclei, their composition, and processes within comets and their nuclei. The material is presented not with the intend to criticize laboratory work simulating condition in comet nuclei, or observers analyzing their observations, nor modelers using data from both these sources to improve our understanding and make predictions. The intent is to provoke discussion and dialog between these groups to avoid overstating the results. What is a Comet? A comet is a diffuse appearing celestial phenomenon moving in an orbit about the Sun. The central body, the nucleus, is composed of ice and dust. It is the source of all cometary activity, including comae and tails. We distinguish between molecular including atoms and ions) and dust comae. At heliocentric distances of about 1 AU and less, the hydrogen coma typically has dimensions larger than the Sun. The tails are composed of dust, neutral atoms and molecules, and plasma.